Pengembangan Teknologi ERP Untuk Accounting Management Dan HRM Pada LAKPESDAM PCNU - nurul aulia hasanah (Resolusi : Rekayasa Teknik Informatika dan Informasi, 2020)
Along with the development of increasingly sophisticated technology and information, the human need for information technology is also getting bigger. The development of information technology can improve performance and support various activities that can be carried out quickly, precisely and accurately, thereby increasing productivity. The role of information technology, which is a combination of communication technology and computer technology, is also indispensable for an institution to assist in carrying out its activities. Financial reports are one of the determinants of program management. The lack of understanding of the system for branch staff also made actual reporting difficult as staff had to do two jobs in two systems each month. With the existing problem, the existence of an information system in an organization will make it easier for staff in branches to report the results of their activities quickly without having to use two systems. Organizations should no longer go through the manual reporting process, because it takes time. ERP software helps organizations automate most of their activities, so that organizations can focus more on meeting activity demands and improving the quality of their flasks.